Evidence-based practice in educating deaf and hard-of-hearing students - Spencer, Patricia Elizabeth; Marschark, Marc. (Oxford ; New York : Oxford University Press, 2010)
""One of the greatest challenges in educating deaf and hard-of-hearing students today is the need for evidence-based practice to replace decades if not centuries of intuitive teaching. This volume will help to move the field of deaf education forward. In it, the authors carefully evaluate the existing literature with regard to deaf education, separating wheat from chaff and knowledge from belief. It points the way forward for teachers and learners of all ages."---T. Alan Hurwitz. President, Gallaudet University" ""An excellent book for both the experienced practitioner or academic and those new to the field of deaf education. As well as addressing the findings of research, it also discusses the research procedures necessary for studies to contribute towards an adequate evidence base. It is an important book, likely to influence practice, and is recommended to all with an interest in the education of deaf children and young people."---Susan Gregory, Former Reader in Deaf Education, University of Birmingham, U.K." "Debates about methods of supporting language development and academic skills of deaf or hard-of-hearing children have intensified in recent years: Will using sign language interfere with learning to use spoken language? Does placement in classrooms with mostly hearing children enhance or impede academic development? Do deaf children need auditory-based phonological skills to acquire age-appropriate reading abilities? Are traditional methods of teaching subjects such as math and science effective for deaf and hard-of-hearing students?" "Too often, these decisions are made based on what is frequently incorrect or incomplete information and decisions---whether based on opinions, beliefs, or value judgments---are insufficient to guide practice. Instead, critical evaluation of the rapidly emerging research and related reports is needed to enhance the success of educational practice with deaf and hard-of-hearing learners. Evidence-Based Practice in Educating Deaf and Hard-of-Hearing Students clarifies and cogently summarizes these research findings across multiple disciplines, providing a comprehensive but concise record of the evidence base in deaf education. These and other questions form the basis for decisions about types of support provided to families and about educational interventions needed to assure deaf and hard-of-hearing children reach their potential." "Evidence (or its lack) on these and other issues is presented concisely in this book in order to provide a focus for future educational and research efforts, and thus to promote optimal developmental support for all deaf and hard-of-hearing children and adults. Co-authored by two of the most respected leaders in their field, this book provides a synthesis of information gathered across a range of settings and uses a variety of research methods in order to define what is known about promising and evidence-based practices in deaf education, and what continues to need investigation. A readily accessible and invaluable source for teachers, university students, and other professionals, Evidence-Based Practice in Educating Deaf and Hard-of-Hearing Students encourages readers to delve more deeply into what we know about deaf and hard-of-hearing children, their patterns of development, and their lifelong learning."--BOOK JACKET.
1. Introduction and Key Findings Index -- Key Findings Index -- 2. Demographics, Diversity, and Foundational Issues in Deaf Education -- A "Low Incidence" Disability -- Deaf and Hard-of-Hearing Children in Countries With Developing Economies -- Multiple Disabilities, or Children With Dual Diagnoses -- Developmental Challenges -- Academic Achievement -- Social-Emotional Development -- Advances in the Development of Deaf and Hard-of-Hearing Students -- Processes of Evaluation -- Summary: Understanding and Educating Children With Hearing Loss -- 3. Evaluating the Evidence in Deaf Education: Methods for Obtaining Trustworthy and Useful Information -- Designs for Research and Evaluation on Educational Practice and Outcomes -- Randomized Clinical Trials, or Experimental Research -- Quasi-Experimental Research -- Single-Subject Research -- Correlational Research -- Qualitative Research -- Practice-Based Wisdom -- Considerations for Studies Included in This Review -- Summary: How Do We Know What We Know? -- 4. Early Identification of Hearing Loss and Early Intervention Services: Implications for Language and Learning -- Newborn Screening and Family Reactions -- Enhanced Developmental Outcomes Related to Early Identification -- How Early Is "Early Enough?" -- Characteristics of Early Intervention That Support Positive Developmental Outcomes -- Summary: Early Identification and Intervention are Cost-Effective -- 5. Language Development, Languages, and Language Systems -- Perspectives on Language Development and Deaf Children -- Approaches Emphasizing Auditory-Oral Aspects of Language Development -- Auditory-Oral Methods and Language Development -- Cochlear Implants and Progress in Oral Programs -- An Example: Outcomes of Children in a Traditional Oral Program -- Auditory-Verbal Therapy -- Cued Speech -- Using Cochlear Implants and Cued Speech -- Approaches Emphasizing Visual-Manual Aspects of Language Development -- Manually Coded Sign Systems Used in Total Communication Programs -- Using Cochlear Implants in TC Programs -- Sign, Sign Bilingual, or "Bilingual/Bicultural" Programming -- The Sign/Bilingual Approach as an Educational Model -- Cochlear Implants and Sign/Bilingual Programming -- Summary: Language Learning in Speech and Sign -- 6. Acquisition and Development of Literacy Skills -- Factors Proposed to Influence Reading Skills -- Early, Interactive, Pre-Literacy Experiences Support Literacy Development -- Phonological Awareness, Phonics, and Literacy Skills -- Emphasizing Auditory Information to Build Phonological Knowledge and Literacy Skills -- Phonological Knowledge and Literacy When Visual Language Input Is Increased -- Vocabulary and Literacy Development -- Syntactic Knowledge and Reading -- Knowledge of a First Language as a Basis for Literacy in a Second Language -- Teaching Approaches and the Development of Reading Comprehension -- Metacognition and Reading Comprehension -- Writing -- Summary: The Continuing Challenge of Literacy -- 7. Cognition, Perception, and Learning Strategies -- Foundations of Learning: Play and Theory of Mind -- Play -- Theory of Mind -- Visual Attention, Language, and Communication -- Memory Processes, Perception, and Learning -- Integrating Information and Using Problem-Solving Strategies -- Responses to Cognitive Intervention -- Summary: On Thinking and Learning -- 8. Achievement in Mathematics and Science -- Mathematics -- Early Development -- Mathematics Development During School Years -- Components of Mathematics Performance -- Mathematics Interventions for Deaf and Hard-of-Hearing Students -- Development of Mathematics Concepts and Skills: Where Are We? -- Science Education and Achievement -- Fostering Science Learning by Deaf and Hard-of-Hearing Students -- Summary: Discoveries in Math and Science -- 9. Educational Placement Decisions and Outcomes -- Student Characteristics, Needs, and Placement Patterns -- Social-Emotional Functioning and Co-Enrollment Programs -- Program Placement and Student Outcomes -- A Co-Enrollment Model -- A Mainstreaming Approach for Students Using Spoken Language -- Special Classrooms, Centers, or Schools: Sign/Bilingual Programming -- Classroom Physical Settings and Acoustic Concerns -- Classroom Interpreting and Real-Time Text -- Summary: The Who, What, and Where of Going to School -- 10. Programming for Children With Multiple Disabilities -- Variability Among Deaf and Hard-of-Hearing Children with Multiple Disabilities -- Children with Cognitive or Intellectual Disabilities -- Cochlear Implants, Cognitive Delays, and Language Development -- Learning Disabilities and Attention Deficit Disorder -- Attention Disorders -- Autism Spectrum Disorders -- Deafblindness -- Congenital Rubella Syndrome -- Genetic/Chromosomal Syndromes -- A Broader View -- Summary: Serving Children with Multiple Challenges -- 11. Issues and Trends in Best Practice.ractice-Based Wisdom -- Considerations for Studies Included in This Review -- Summary: How Do We Know What We Know? -- 4. Early Identification of Hearing Loss and Early Intervention Services: Implications for Language and Learning -- Newborn Screening and Family Reactions -- Enhanced Developmental Outcomes Related to Early Identification -- How Early Is "Early Enough?" -- Characteristics of Early Intervention That Support Positive Developmental Outcomes -- Summary: Early Identification and Intervention are Cost-Effective -- 5. Language Development, Languages, and Language Systems -- Perspectives on Language Development and Deaf Children -- Approaches Emphasizing Auditory-Oral Aspects of Language Development -- Auditory-Oral Methods and Language Development -- Cochlear Implants and Progress in Oral Programs -- An Example: Outcomes of Children in a Traditional Oral Program -- Auditory-Verbal Therapy -- Cued Speech -- Using Cochlear Implants and Cued Speech -- Approaches Emphasizing Visual-Manual Aspects of Language Development -- Manually Coded Sign Systems Used in Total Communication Programs -- Using Cochlear Implants in TC Programs -- Sign, Sign Bilingual, or "Bilingual/Bicultural" Programming -- The Sign/Bilingual Approach as an Educational Model -- Cochlear Implants and Sign/Bilingual Programming -- Summary: Language Learning in Speech and Sign -- 6. Acquisition and Development of Literacy Skills -- Factors Proposed to Influence Reading Skills -- Early, Interactive, Pre-Literacy Experiences Support Literacy Development -- Phonological Awareness, Phonics, and Literacy Skills -- Emphasizing Auditory Information to Build Phonological Knowledge and Literacy Skills -- Phonological Knowledge and Literacy When Visual Language Input Is Increased -- Vocabulary and Literacy Development -- Syntactic Knowledge and Reading -- Knowledge of a First Language as a Basis for Literacy in a Second Language -- Teaching Approaches and the Development of Reading Comprehension -- Metacognition and Reading Comprehension -- Writing -- Summary: The Continuing Challenge of Literacy -- 7. Cognition, Perception, and Learning Strategies -- Foundations of Learning: Play and Theory of Mind -- Play -- Theory of Mind -- Visual Attention, Language, and Communication -- Memory Processes, Perception, and Learning -- Integrating Information and Using Problem-Solving Strategies -- Responses to Cognitive Intervention -- Summary: On Thinking and Learning -- 8. Achievement in Mathematics and Science -- Mathematics -- Early Development -- Mathematics Development During School Years -- Components of Mathematics Performance -- Mathematics Interventions for Deaf and Hard-of-Hearing Students -- Development of Mathematics Concepts and Skills: Where Are We? -- Science Education and Achievement -- Fostering Science Learning by Deaf and Hard-of-Hearing Students -- Summary: Discoveries in Math and Science -- 9. Educational Placement Decisions and Outcomes -- Student Characteristics, Needs, and Placement Patterns -- Social-Emotional Functioning and Co-Enrollment Programs -- Program Placement and
Includes bibliographical references and index.
Keywords: Deaf children -- Education; Hearing impaired children -- Education; Deaf children -- Education; Hearing impaired children -- Education